Pengembangan Media Pembelajaran Interaktif Pada Materi Gelombang Cahaya Berbasis Android Menggunakan Articulate Storyline 3 - Amalia, Dhea Dina; Riswanto, Riswanto; Alarifin, Dedy Hidayatullah (JURNAL FIRNAS, 2020)
Abstract : This development research aims to develop interactive learning media in the form of links that can be opened by students when studying light waves, especially in light polarization sub-materials that are suitable for use in the learning process. The interactive learning media produced from this development research aims to make learning more fun and students do not feel bored when learning takes place. Development research is a research method that produces or develops a particular product with the aim of testing the effectiveness of the product that has been developed. The research model used is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research was conducted by developing interactive learning media products using the Articulate Storyline 3 application. The developed product has been validated by media experts and material experts to get an average percentage score of 86.25%. The validation results show that the media is very feasible to use in learning, it is reviewed based on the results from the aspect of learning objectives and aspects of language. The results of the student response trial get an average percentage of 82%. Shows that the product is very attractive to students, it is reviewed based on the results from the design aspect